TINJUAN YURIDIS PENGEMBANGAN SISTEM PERADILAN PIDANA DALAM RUU KUHAP - Setiady, Tri (Universitas Wiralodra, 2013)
Thirty years after the Criminal Code enacted in Indonesia . Law No. 8 of 1981 on the statute books of the criminal procedure law enforcement initially seen as a